KOMUNIKASI ANTARPRIBADI PASANGAN JARAK JAUH DALAM MEMPERTAHANKAN HUBUNGAN PASCA PERSELINGKUHAN DI KALANGAN MAHASISWA KOTA PEKANBARU - Handayani "; Nita Rimayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Interpersonal communication between long-distance couples in maintaining post-infidelity relationships among Pekanbaru City students will determine the quality of long-distance partner relationships and is the key to the success of long-distance couples in maintaining relationships after the affair occurs. Long distance couples have a very close relationship and communication that takes place in harmony and open. This is done so that there will be no more infidelity in the future or conflicts that can become problems in the relationships that have been fostered. The approach used in this research is to use a humanistic approach according to Devito. The purpose of this study was to determine the attitude of openness in long-distance couples in maintaining post-infidelity relationships, empathy attitudes in long-distance couples in maintaining post-affair relationships, supportive attitudes towards long-distance couples in maintaining post-infidelity relationships, positive attitudes in long-distance couples in maintaining post-infidelity relationships and equality in long-distance partners in maintaining post-infidelity relationships.This research uses descriptive qualitative research. Determination of informants using purposive sampling method. Data collection techniques in this study are in-depth interviews, observation, and documentation. Data analysis techniques are interpreted by data reduction, data presentation and conclusion drawing. The technique of checking the validity of the data used the triangulation method.The results of this study indicate that interpersonal communication between couples who undergo long-distance relationships in maintaining the post-infidelity relationship can take place according to circumstances in terms of mutually maintaining or achieving goals as expected. self-openness is carried out by means of communication via chat via WhatsApp and video calls on a regular basis, empathy admits mistakes to partners and holds a commitment to a relationship to improve each other, a supportive attitude provides solutions and assistance to partners when there is a problem and is sensitive to the situation of the partner contact your partner when your partner has an activity that takes a long time and send photos or videos of activities and give gifts or praise as appreciation. Equality discuss when there are differences and allow time for self-reflection to each if there is a debate.